Preventing Bankruptcy of Insurance Companies in IndonesiaUsing ‎The COSO Framework Approach (Case Study of AJB Bumiputra)‎ - Amrizal; Agustina, Yumni; Hardi (International Journal of Accounting and Economics Studies, 2025)
Background: The financial crisis at the AJB Bumiputra 1912 insurance company ‎in Indonesia has attracted the attention of academics to seek recovery solutions.‎Objective: Examining the root causes of the financial crisis and solutions for the ‎insurance company AJB Bumiputra 1912‎.Methodology: Qualitative research design, data collection through in-depth ‎interviews and documentation. Data analysis using design thinking as an ‎alternative problem-solving methodology.‎The financial crisis, marked by the failure to pay customer claims amounting to $ ‎‎32 trillion, occurred due to mismanagement and violations of the provisions ‎outlined by the Committee of Sponsoring Organizations, particularly the Control ‎Environment principle. This includes a decline in management integrity, which has ‎shifted from upholding the values of collective effort and cooperation to ‎individualism, collusion in the management structure, and dual roles where ‎commissioners concurrently serve as interim directors. The Company's recovery ‎from the financial crisis was carried out by selling fixed assets into liquid assets, ‎reducing the value of benefits for policyholders, rationalizing HR, and ‎restructuring the organization. Strengthening Management by implementing the ‎COSO Framework properly, so that the Company returns to the basic values of the ‎Company's founding, as outlined by its founding father.‎Contribution: The research findings can serve as a reference for AJB Bumiputra ‎‎1912 to help it recover from the financial crisis‎.
Keywords: Mutual Funds; Control Environment; Risk Assessment; Control Activities; ‎Monitoring Activities